2019
DOI: 10.1590/1414-431x20198224
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Leishmania spp in Lutzomyia longipalpis in the city of Lavras, Minas Gerais, Brazil

Abstract: Leishmaniasis is a neglected disease that affects a large part of the world population. Knowing the sand fly fauna of a region is of fundamental importance for guiding health surveillance actions related to the prevention and control of leishmaniasis. A total of 86 specimens of sand flies (60 females and 26 males) were collected. Using the classification proposed by Galati (2003), the following species were identified: Lutzomyia longipalpis (Lutz & Neiva, 1912), Migonemyia mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…As in Santa Catarina, in areas previously considered non-endemic for CVL in other states of Brazil (Steindel et al, 2013;Maziero et al, 2014), showed a similar situation when using the PCR technique for the testing of dogs as recorded in some municipalities of Rio de Janeiro (De Paula et al, 2009;Campos et al, 2013) and Minas Gerais (Castro et al, 2019). In the metropolitan region of Porto Alegre (RS), a non-endemic region, a prevalence of 4% was observed through real time PCR and serology, being the essential molecular method for excluding false negatives and false positives (Riboldi et al, 2018).…”
Section: Discussionsupporting
confidence: 57%
“…As in Santa Catarina, in areas previously considered non-endemic for CVL in other states of Brazil (Steindel et al, 2013;Maziero et al, 2014), showed a similar situation when using the PCR technique for the testing of dogs as recorded in some municipalities of Rio de Janeiro (De Paula et al, 2009;Campos et al, 2013) and Minas Gerais (Castro et al, 2019). In the metropolitan region of Porto Alegre (RS), a non-endemic region, a prevalence of 4% was observed through real time PCR and serology, being the essential molecular method for excluding false negatives and false positives (Riboldi et al, 2018).…”
Section: Discussionsupporting
confidence: 57%
“…The south of Minas Gerais, where Carrancas is located is considered endemic for VL and has a relatively high diversity of sandflies. For example, the municipality of Lavras, a city in the same region and considered a focus of recent transmission, has already reported 14 different species of sandflies (Barçante et al, 2018;Milagres et al, 2018;Castro et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Although it is considered the main transmitting species of L. infantum in the Americas, in some regions, positive human and dog cases have been verified in areas without L. longipalpis, as is the case in Jaciara, Mato Grosso, where the species L. cruzi seems to be mainly responsible for cycle transmission (Missawa et al 2011), and in Corumbá, Mato Grosso do Sul, where L. cruzi was identified as a vector of L. infantum (Oliveira et al 2016). In addition, there is strong evidence that other species, such as Migonemyia migonei (França, 1920), Pintomyia fischeri (Pinto, 1926), Lutzomyia gaminarai (Cordero et al 1928) and Nyssomyia intermedia (Lutz & Neiva, 1912), play a role in the transmission of L. infantum in some areas (Carvalho et al 2010, Saraiva et al 2010, Brasil 2014, Moya et al 2015, Galvis-Ovallos et al 2017, Castro et al 2019, 2020, Galvis-Ovallos et al 2021, Milagres et al 2022.…”
Section: Discussionmentioning
confidence: 99%